APPLICATION OF A MULTIPLE SCATTERING MODEL TO ESTIMATE OPTICAL DEPTH, LIDAR RATIO AND ICE CRYSTAL EFFECTIVE RADIUS OF CIRRUS CLOUDS OBSERVED WITH LIDAR - Gouveia, Diego; Baars, Holger; Seifert, Patric; Wandinger, Ulla; Barbosa, Henrique; Barja Gonzalez, Boris; Artaxo, Paulo; Lopes, Fabio; Landulfo, Eduardo; Ansmann, Albert (My University, 2018)
Lidar measurements of cirrus clouds are highly influenced by multiple scattering (MS). We therefore developed an iterative approach to correct elastic backscatter lidar signals for multiple scattering to obtain best estimates of single-scattering cloud optical depth and lidar ratio as well as of the ice crystal effective radius. The approach is based on the exploration of the effect of MS on the molecular backscatter signal returned from above cloud top.
Keywords: Cirrus; Backscatter (email); Effective radius; Ranging